Active pollinator choice by Heliconia 'fits the bill'. (July 2015) - Bronstein, Judith L.; Richman, Sarah K.
<x xml:space="preserve">Abstract</x> A new study documents that a tropical plant only reproduces when pollen has been deposited by a visitor capable of extracting nectar from its deep flowers. Large, long-billed hummingbirds generally carry greater quantities of, and more genetically diverse, pollen. Thus, plants can exert more active partner choice than previously considered possible.